2022
DOI: 10.1136/jim-2021-002289
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides, Oxidative Stress Biomarkers, and Leukemia: A Case-Control Study

Abstract: Exposure to pesticides has been linked to an elevated risk of leukemia. The present research aimed to evaluate the relationship between organochlorine (OC) pesticides and biomarkers of oxidative stress in patients with leukemia. This work was conducted on 109 patients with leukemia and 109 healthy controls. The serum concentrations of seven derivatives of OCs including alpha-hexachlorocyclohexane (HCH), beta-HCH, gamma-HCH, 2,4-dichlorodiphenyltrichloroethane (DDT), 4,4-DDT, 2,4-dichlorodiphenyldichloroethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
1
0
0
1
Order By: Relevance
“…The escalation of OS could also lead to lipid peroxidation and an elevate in its end-products, such as MDA. It has been established that exposure to pesticides can augment MDA levels by triggering OS (40). The present study found that MDA levels were significantly higher in the patient group than in the control, suggesting that these patients may have been exposed to pesticides.…”
Section: Discussionsupporting
confidence: 51%
“…The escalation of OS could also lead to lipid peroxidation and an elevate in its end-products, such as MDA. It has been established that exposure to pesticides can augment MDA levels by triggering OS (40). The present study found that MDA levels were significantly higher in the patient group than in the control, suggesting that these patients may have been exposed to pesticides.…”
Section: Discussionsupporting
confidence: 51%
“…Se ha documentado la asociación entre la exposición a plaguicidas y el riesgo leucemia (Foucault et al, 2021). La exposición a plaguicidas aumenta los niveles de especies reactivas de oxígeno (ROS), lo que conduce a un incremento del estrés oxidativo, el cual desempeña un papel importante en la aparición y progresión de leucemia al estimular la supervivencia celular, señalización de crecimiento y la inestabilidad genómica (Kreitz et al, 2019;Rafeeinia et al, 2022). Desafortunadamente, en México no existen estudios previos que evalúen leucemia en personas expuestas a plaguicidas.…”
Section: Discussionunclassified